PENAMAAN DALAM BAHASA INGGRIS DAN BAHASA SANGIHE (SUATU ANALISIS KONTRASTIF) - Tahumil, Muktar; Lotulung, Donald R.; Rattu, Jultje A. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2021)
Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â ABSTRACTÂ  Â  Â  Â  Â  Â  Muktar Tahumil1 , Donald R. Lotulung2 , Jultje A. Rattu3This research entitled â€œPenamaan dalam Bahasa Inggris dan Bahasa Sangihe: Suatu Analisis Kontrastifâ€. The aim of this research is to make a contrastive analysis of Toponym in English and Sangihe Language. In analysing the data from two languages, the writer used the theory from Tent & Slatyer (2009:22) and Fraenkel & Wallen (1993. P.23) to contrast both languages. Some previous study which also been used to support this research, Suripatty (2015) and Prayogo, et al (2016). The descriptive qualitative method is used to describe the data analysis. The finding shows that the similarity between two languages is laid only in the category of toponym and there are three differences: descriptive toponym is more common in Sangihe language while in English more likely to used eponymous toponym, toponym in English more likely to used literal meaning while Sangihe language convey figurative meaning and the evaluative, indigenous, also shift toponym category are not found in Sangihe language.Keywords : Toponym, English and Sangihe language, Contrastive Analysis.Â